IMPLEMENTASI PROGRAM PEMBERDAYAAN USAHA GARAM RAKYAT (PUGAR) DI DESA KEDUNGMUTIH KECAMATANWEDUNG KABUPATEN DEMAK TAHUN 2011- 2013 - Yunita Ratna Sari; Budi Setyono; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2015)
AbstractGovernment policy to import salt in order to fulfill the national need has caused saltfarmers live in a poor condition, like the ones living in Kedungmutih village. This village hasbeen known as a hot spot area of poverty because its people, working as a fisherman and saltfarmer, only rely on salt production to fulfill their daily need. PUGAR program held in 2011 atKedungmutih village was hoped to be able to increase the salt farmers’ prosperity. This researchaims to investigate “How is the implementation of PUGAR program at Kedungmutih village,Wedung sub-district, Demak regency in 2011-2013?” and “What are the obstacles in theimplementation of PUGAR program in Kedungmutih village, Wedung sub-district, Demakregency in 2011-2013?”.The purpose of this research is to know how PUGAR program is implemented and itsobstacles when held at Kedungmutih village, Wedung sub-district, Demak regency in 2011-2013. This research used qualitative-explorative method. There were two kinds of data, theprimary data, collected from interview with the informant or key person using snowballsamplings and the secondary data, collected from documents, archives, and other sources relatedto the research. Technique of analysis used in this research was qualitative data analysisconducted in the form of description and conclusions of the researched phenomena.The result of the research showed that “PUGAR” program at Kedungmutih village heldin 2011-2013 is less optimal because there are unresolved problems. These problems are saltfarmers’ inability in applying technology in salt production, problems in marketing due to theexistence of middlemen, and salt farmers’ inability to produce the best quality salt (KW1). Therecommendations are that the Salt Farmers Assistant Team should assist salt farmers in applyingtechnology in salt farming and that it is necessary for the government to establish salt farmers’cooperative (KOGAR).Keywords: Implementation, Empowerment, Salt Farmers